PENGARUH PELET ISONIAZID LEPAS TUNDA TERHADAP KETERSEDIAAN HAYATI RIFAMPISIN SECARA IN VIVO PADA TIKUS WISTAR JANTAN - Rahmawati, Mega
Isoniazid (INH) in combination with rifampicin (RIF) gives an effective dose regiment for tuberculosis therapy. However, when consumed together, INH and RIF could undergo an interaction that lead into a lower bioavailability of RIF. This problem can reduce the efficacy of therapy and might increase the risk of drug resistance. This study was aimed to make INH delayed released pellets and to evaluate its effect to RIF bioavailability when administered together to male Wistar rats. Isoniazid pellets containing 55% and 70% drugs were developed by wet granulation, extrusion, and sferonization method. Enteric coating system consisted of Opadryle Clear 03K19229 as a seal coat and Sureteric® as an enteric coat. The effectivity of enteric coating system was evaluated by in vitro testing using type 3 Dissolution Apparatus in HC1 0.1 N and phosphate buffer pH 6.8. INH concentrations were determined using spectrophotometric UV method. Bioavailability of RIF in the presence of INH was evaluated in rats which were divided into three groups. The first group received RIF (n=5), the second group received together with uncoated INH pellets (n=5), whereas the third group received RIF together with delayed released INH pellets (n=5). Blood samples were collected from femoral artery prior to drug administration and at 0.25; 0.5; 1; 1.5; 2; 3; 4; 6; 8; 10; 12 h after drug administration. RIF concentrations in plasma were determined by HPLC. Formula of delayed released INH pellets with 4% Opadry Clear 03K19229 and 60°/0 Sureteric weight gain could prevented INH release in acid medium to only 4.06 %, then released 'NH up to 95.04 + 4.16% after 45 min in phosphate buffer. Mean AUCo_12 obtained were 39.27 1 10.30 .tg/mL h (n=4), 13.17 + 3.35 rig/mL.h (n=4), 30.66 + 2.42 ug/mL.h (n=5) from the first, second, and third group, respectively. Delayed released INH pellets prevented the released of INH from high loading dose pellets in acid medium and increased the biovailability of rifampicin, with significant differences when compared to the second group.